High- versus low-intensity resistance exercise in the treatment of pain in patients with knee osteoarthritis: Exercício resistido de alta versus baixa intensidade no tratamento da dor em pacientes com osteoartrite de joelho - De Sá, Clodoaldo Antônio; Grossl, Fernando Schorr; Vasconcelos , Alan Bruno Silva; Copatti , Sedinei Lopes; Corbellini , Felipe; Corralo, Vanessa da Silva (Revista FisiSenectus, 2024)
Objective: To compare the effects of two intervention protocols using a single low- (LIRE) or high- (HIRE) intensity resistance exercise on chronic pain and muscle strength in patients with knee osteoarthritis (KOA). Methods: Twenty patients with a clinical diagnosis of KOA were evaluated and randomized into two intervention groups: (HIRE: N=10, 75% of 1-RM; LIRE: N=10, 30% of 1-RM). Each group performed a single resistance exercise (knee joint extension on a leg extension machine) at high or low intensity twice a week. Strength for one repetition maximum (1-RM), functional strength, and pain were assessed before and after 12 weeks of intervention. Results: Pain decreased from pre- to post-test in both the ERBI group (effect size = -1.931) and the HIRE group (effect size = -3.299), and this reduction was significantly greater in the HIRE group (p > 0.05). Both HIRE and LIRE produced increases in 1-RM strength and functional strength after 12 weeks of intervention (p < 0.05). The percentage change between pre- and post-test for functional strength showed a negative correlation with the percentage change in pain only in response to high-intensity exercise (p < 0.05). Conclusions: ERAI is more effective than ERBI in reducing pain in patients with KOA. Increased functional strength is associated with greater pain reduction only in response to HIRE.